3D-printed Biphasic Calcium Phosphate Scaffold to augment cytocompatibility evaluation for load-bearing implant applications - Ananth K.P.; Jayram N.D.; Muthusamy K. (Elsevier Inc., 2025)
In this work, we developed and analyzed a biphasic calcium phosphate (BCP) bioceramic for bone regeneration using stereolithography (SLA). The SLA method is a promising additive manufacturing (AM) technique capable of creating BCp parts with high accuracy and efficiency. However, the ceramic suspension used in SLA exhibits significantly higher viscosity and is not environmentally friendly. Therefore, adequate preparation of a suspension with low viscosity and high solid loading is essential. In this paper, we optimized the effects of surfactant doses and solid loading on the BCp slurry, and initially examined the process parameters of photocuring, debinding, and sintering. The utilization of 9 wt % Disperbyk (BYK) with a 40 vol % loading of BCp bioceramics exhibited a reasonably low viscosity of 8.9 mPas at a shear level of 46.5 s?1. Functional and structural analyses confirmed that BCp was retained after photocuring and subsequent treatment, which were incorporated into the BYK dispersion. The 3D printed objects with different sintered temperatures, specifically at 1100 C, 1200 C, and 1300 C, were further optimized. Additionally, the surface roughness, porosity, and mechanical properties of BCp green parts were systematically investigated. Most importantly, in vitro analysis of cell attachment, differentiation, and red alizarin analysis could support the application of bone regeneration. ? 2024 The Author(s)